Occupational activity during pregnancy based on the Polish Mother and Child Cohort Study - Kinga Polańska; Joanna Jurewicz; Andrzej Marcinkiewicz; Teresa Makowiec-Dąbrowska; Wojciech Hanke (Nofer Institute of Occupational Medicine, 2014)
Background: In Poland conditions related to or aggravated by the pregnancy, childbirth or the puerperium are one of the most common causes of sickness absence. The aim of the study was to analyze the occupational activity pattern during pregnancy and to evaluate the determinants of pregnancy-related temporary work disability confirmed by medical certificate. Materials and Methods: The presented analysis is based on data collected under the Polish Mother and Child Cohort Study. The study population consisted of 954 women who reported occupational activity during pregnancy. All women participating in the study were interviewed 3 times during pregnancy. Detail information on occupational activity during pregnancy and occupational stress, based on the Subjective Work Characteristics Questionnaire, was collected from all women. Results: The pregnant women had been issued medical certificate of temporary work disability because of conditions related to or aggravated by the pregnancy, childbirth or by the puerperium at 16 week of gestation on average and did not continue their activities until the end of pregnancy. The statistically significant determinants of receiving such medical certificate in the first trimester of pregnancy (≤ 12 weeks of pregnancy) comprised poor health condition and complications during pregnancy (OR = 1.4; p = 0.01), lower education (OR = 2.4; p < 0.001), socio-economic status (OR = 9.6; p = 0.03), use of public transport to commute to work (OR = 2.7; p < 0.001), a longer work commute (OR = 1.4; p = 0.008) and a higher level of occupational stress (OR = 3.0; p < 0.01). Waitresses, nurses and saleswomen received medical certificate of temporary work disability in the first trimester of pregnancy more frequently than office workers (OR = 4.2; p = 0.005; OR = 3.3; p = 0.02; OR = 2.3; p < 0.001 respectively). Conclusions: It is crucial to develop the model of cooperation between occupational medicine physicians and gynecologists and a greater involvement of the former in the prophylactic care of occupationally active pregnant women. It is also important to increase the employers' awareness of potential risks and arduousness at work to assure working conditions safe for the pregnancy outcome and health of both women and their babies. Med Pr 2014;65(1):65-72